Insulating Materials : Principles, Materials, Applications - Gellert, Roland; Rudolphi, Alexander; Spitzner, Martin (Birkhäuser, 2012)
Detail Practice: Insulating Materials offers a comprehensive catalogue of insulating materials for use in construction. Notes on the individual types of insulating materials provide information on the raw materials they contain as well as their typical attributes, areas of application, and delivery forms.